A systems-based approach to address unintended consequences of demand-driven transportation planning in national parks and public lands. Issue 2 (7th February 2017) - Lawson, Steven R.; Newman, Peter; Monz, Christopher
ABSTRACT: In most cases, transportation planning in national parks and public lands might most appropriately be termed "demand-driven." In this approach, rigorous analyses of park visitation, traffic, and parking data are used as a basis for transportation planning to accommodate current and projected future visitor demand, within financial constraints. Performance measures used to assess the quality of transportation systems in national parks are generally related to "moving people" efficiently. This approach is based on well-established principles for transportation planning in urban and rural communities. However, a demand-driven approach to transportation planning may not be suitable in national parks and public lands because it may enable levels of visitation that cause visitor crowding, resource impacts, and other unintended consequences. This paper introduces a more sustainable, systems-based transportation planning approach developed in the Rocky Mountain National Park (ROMO) to help the park operate its shuttle bus system efficiently and conveniently, and according to thresholds for visitor crowding and resource impacts at sites serviced by the shuttle system. The transportation planning approach developed in this study for ROMO is more suitable and sustainable for national parks and public lands than a demand-driven approach, and is readily adaptable to other locations. Correspondingly, the approach is now being applied in several other national parks and public lands recreation areas.